Efeito dos nutrientes (nitrogênio e fósforo) sobre o desenvolvimento da Gracilaria birdiae: crescimento e possível uso como biofiltro - Nunes, Sdena Oliveira (2006)
Marine shrimp farming has grown exponentially during the last years in Brazil. In spite of the promising economical situation, this activity is facing an increasing criticism due to its environmental impact. Thus, the necessity of alternatives to mitigate environmental degradation caused by this activity. An alternative that is being studied is the policulture that is the integrated culture of two or more organisms, normally one of them a filtering organism. Among filtering organisms, macroalgae are very practicable because they are efficient in the removal of the exceeding nutrients of the water and do not leave residues in the water. Besides, the integrated culture with macroalgae allows the economical exploration of the seaweed (for the manufacture of jelly and jam, for the dairy industry, pharmaceuticals, etc.) along with possibility of a sustainable aquaculture. In the present experiment, the development of the seaweed Gracilaria birdiae, the influence and tolerance of this species to the environmental parameters, and its absorption efficiency in relation with the three kinds of macronutrients (NH4+, NO3- and PO4-3) found in the effluents of marine shrimp farming was studied. The experiment was divided in two parts: a laboratorial part and one part carried under natural conditions. The water used in the laboratory trial was collected in the shrimp ponds of Tecnarão farm and distributed in aquaria containing 20 g of G. birdiae. In the field trial, 0.5 kg of G. birdiae was inserted in PVC cages cultivated in the farm. The results of the study showed a modest growth of G. birdiae, probably due to its low tolerance to highly eutrophicated environments. However, the removal of nutrients was very expressive. Ammonia was reduced in approximately 34 %. Ortho-phosphate showed a reduction of 93.5 %. The capacity of biofiltration of the NO3- by the macro algae was of 100 %, showing that G. birdiae is a seaweed-filtered with a high level of removal for this nutrient under laboratorial conditions. In spite of the low growth of the macro algae in the experiment, the results in relation to the removal of nutrients of the water was encouraging, suggesting that this species can be an efficient biofilter and thus, a strong candidate to be used in a sustainable aquaculture